Botanical-Based Strategies for Controlling Xanthomonas spp. in Cotton and Citrus: In Vitro and In Vivo Evaluation - Roeschlin, Roxana Andrea; Favaro, María Alejandra; Bertinat, Bruno; Lorenzini, Fernando; Paytas, Marcelo Javier; Fernandez, Laura Noemí; Marano, María Rosa; Derita, Marcos Gabriel (MDPI, 2025)
Citrus canker, caused by Xanthomonas citri subsp. citri, and bacterial blight, caused by Xanthomonas citri subsp. malvacearum, results in substantial economic losses worldwide, and searching for new antibacterial agents is a critical challenge. In this study, regional isolates AE28 and RQ3 were obtained from characteristic lesions on Citrus limon and Gossypium hirsutum, respectively. Essential oils extracted by steam distillation from the fresh aerial parts of Pelargonium graveolens and Schinus molle exhibited complete (100%) inhibition of bacterial growth in vitro at a concentration of 1000 ppm, as determined by diffusion tests. To evaluate the potential of these essential oils for controlling Xanthomonas-induced diseases, in vivo assays were conducted on lemon leaves and cotton cotyledons inoculated with the regional AE28 and RQ3 strains. Two treatment approaches were tested: preventive application (24 h before inoculation) and curative application (24 h after inoculation). Preventive and curative treatments with P. graveolens essential oil significantly reduced citrus canker severity, whereas S. molle essential oil did not show a significant reduction compared to the control. In contrast, regardless of the treatment’s timing, both essential oils effectively reduced bacterial blight severity in cotton cotyledons by approximately 1.5-fold. Gas chromatography–mass spectrometry (GC-MS) analysis identified geraniol and citronellol as the major components of P. graveolens essential oil, while limonene and t-cadinol were predominant in S. molle. These findings highlight the promising potential of botanical products as bactericidal agents, warranting further research to optimize their application and efficacy.